2021
DOI: 10.1177/00111287211007732
|View full text |Cite
|
Sign up to set email alerts
|

Post-Release Source of Income and Convictions of Formerly Incarcerated Adults

Abstract: This study examines the relationship between post-release source of income and convictions for different types of crime. Longitudinal data from a sample of formerly incarcerated adults ( n = 10,879) released from Dutch prisons were used. Fixed effects models show that, compared with receiving social benefits, post-release employment is associated with a lower probability of convictions for crime in general, and for property crime. Persons who are not employed and do not receive benefits have a higher likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Uggen (2000) used a survey of people with arrest histories in the U.S. and found that employment reduced recidivism for those above age 27. Verweij, Weijters, and Wermink (2021) used a sample of prisoners from Dutch prisons and found that employment decreased the likelihood of recidivism. Visher & Courtney (2007) used a survey of released prisoners from Ohio and discovered that employment was a key factor that reduced the probability of being reincarcerated.…”
Section: Literature On Collateral Consequencesmentioning
confidence: 99%
“…Uggen (2000) used a survey of people with arrest histories in the U.S. and found that employment reduced recidivism for those above age 27. Verweij, Weijters, and Wermink (2021) used a sample of prisoners from Dutch prisons and found that employment decreased the likelihood of recidivism. Visher & Courtney (2007) used a survey of released prisoners from Ohio and discovered that employment was a key factor that reduced the probability of being reincarcerated.…”
Section: Literature On Collateral Consequencesmentioning
confidence: 99%
“…The literature on reentry to the community after release from prison confirms that recidivism is lower among those who find stable, high-quality employment (Berg & Huebner, 2011;La Vigne et al, 2004;Lockwood et al, 2012;Uggen, 2000;Verweij et al, 2021;Visher & Courtney, 2007;Visher et al, 2011). The relationship between employment and desistance is especially salient when individuals work in "career jobs" rather than "survival jobs" (Bucklen & Zajac, 2009;Niebuhr & Orrick, 2020;Uggen, 1999) .…”
Section: Introductionmentioning
confidence: 99%